2001
DOI: 10.1103/physreve.64.016414
|View full text |Cite
|
Sign up to set email alerts
|

Neutron energy spectra from the laser-inducedD(d,n)3Hereaction

Abstract: Detailed neutron energy spectra were measured for the D(d,n)3He reaction induced in solid (CD2)(n) targets by irradiation with 50-fs 2 x 10(18) W/cm(2) light pulses from a 10-TW Ti:Sapphire laser. The neutrons were observed at two angles 5 degrees and 112 degrees relative to the incident laser beam. The neutron spectra at the two angles are characterized by peaks with large widths of about 700 keV full width at half maximum and a shift of 300 keV between them. Neutron energies of up to about 4 MeV were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 25 publications
6
31
0
Order By: Relevance
“…The tracks were counted with an optical microscope for the neutron yield. Assuming an isotropic neutron emission, the neutron yield is calculated to be 9 × 10 3 per shot in 4 sr, which is very close to the maximum reported neutron yield of 10 4 per shot [8] under similar experimental conditions as in the present case. The generation of neutrons from the CD 2 target was also registered in the bubble detector kept at 20 mm distance from the target.…”
Section: Methodssupporting
confidence: 69%
See 1 more Smart Citation
“…The tracks were counted with an optical microscope for the neutron yield. Assuming an isotropic neutron emission, the neutron yield is calculated to be 9 × 10 3 per shot in 4 sr, which is very close to the maximum reported neutron yield of 10 4 per shot [8] under similar experimental conditions as in the present case. The generation of neutrons from the CD 2 target was also registered in the bubble detector kept at 20 mm distance from the target.…”
Section: Methodssupporting
confidence: 69%
“…Pretzler et al [7] have observed more than 140 neutrons per laser shot with a laser of 200 mJ pulse energy and 160 fs time duration. Similar type of experiment was also performed by Hilscher et al [8]. They observed a maximum of 10 4 neutrons in a single laser shot.…”
Section: Introductionsupporting
confidence: 61%
“…The evaluation concerning the number of nuclear events is in good agreement with the values obtained in previous experiments and with literature data [12][13][14][15][16][17][18][19][20][21][22]. Fig.…”
Section: Resultssupporting
confidence: 89%
“…To simplify the calculations, we assume: 1) the incident beam of ions exhibits azimuthal symmetry about the axis perpendicular to the secondary target, 2) a straight-line ion trajectory, and 3) neutron production is dominated by D(d,n) 3 He fusion events. Assumption number one is justified by the symmetry of the laser pulse incident upon the uniform target, and from this assumption we may further deduce that the emitted neutron spectrum will similarly exhibit azimuthal symmetry.…”
Section: Calculation Methodsmentioning
confidence: 99%